Changing attitudes to secularization processes within the theory of modernization of religion - Medvedyeva, Yuliya (Ukrai͏̈ns'ke relihijeznavstvo, 2020)
The article considers the key factors in development of the religious situation in the second half of the twentieth century, which caused a radical change in the attitude to the theory of secularization by sociologists of religion. From the beginning, the theory of secularization was a core part of the general theory of modernization and marked the specifics of modernization`s impact on religious life. However, the inability to explain such phenomena as the sharp rise in religiosity in post-socialist countries, as well as the consistently high level of religiosity in the typically modernist United States, led researchers to abandon the classical theory of secularization. Another reason for the change in the attitude to secularization was the presence of a religious component in numerous political conflicts in the late twentieth and early twenty-first centuries. The religious factor in the conflicts was so unusual and decisive that under its influence the theory of "clash of civilizations" by S. Huntington was born at the end of the twentieth century. Even though the general theory of modernization has not disappeared and still remains popular among sociologists of religion, there is no clear reference to the theory of secularization. Secularization is considered either a random part of modernization processes at certain stages, or one of the options for the development of the religious situation along with counter-secularization, or even completely rejected as a false positivist construct that has not been validated with the real state of affairs.